PROJEÇÕES DA PERDA DE SOLO NO ESTADO DO PARANÁ AO LONGO DO SÉCULO XXI, POR MEIO DA SIMULAÇÃO DA EROSIVIDADE EM CENÁRIOS DE MUDANÇAS CLIMÁTICAS - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
Soil loss due to water erosion affects regional development significantly, resulting in extensive losses in the countryside and in the city. Therefore, the objective of this work to estimate and project erosivity in the various regions of the state of Paraná up to the year 2100, as well as to simulate the loss of soil in watersheds with different uses. Rainfall data from 28 meteorological stations scattered throughout the state were used, which allowed for the simulation of daily rainfall, which were used in the pluviometric method to estimate the rainfall erosivity up to 2100, considering two future scenarios conditioned to the global temperature increase. From the values of erosivity, the possibility of estimating and also designing data for soil loss in two watershed with different uses is opened, one where agricultural activity predominates and another, mostly occupied by native forest and reforestation. It was verified the great variation in rainfall erosivity estimation in the different sites of the state, both in the first and in the second scenario, presenting respectively the minimum of 6,157.15 MJ mm ha-1 h-1 ano-1 for the wheather station of Telemaco Borba and maximum value of 17,522.30 MJ mm ha-1 h-1 ano-1 in the wheather station of Francisco Beltrão, at the end of the 21st century. While the average values for soil loss in the sub-basins where agriculture and native forest predominate were, respectively, 1.17 t.ha-1.ano-1 and 51.06 t.ha-1.ano-1 for a more drastic scenario, until 2100. The analysis of the data allowed to evaluate that the erosivity in the state of Paraná will reach a critical value in the southwest region and tends to decrease from the west to the east, being in the coastal plain. The increase of erosivity will be significant as a consequence of the locally differentiated climatic conditions, besides a local study to point out the great variation in the loss of soil in microcatchments of the same region due to the complexity of the causal factors.
Keywords: erosão hídrica; erosividade; perda de solo; mudanças climáticas; erosion; erosivity; soil loss; climate change; CNPQ::ENGENHARIAS